The Influence of Smart Car Technologies on Drivers' Perceived Control and Attachment - So-Eun Lee; Seongcheol Kim (International Telecommunications Society (ITS), 2017)
Connected to various media technologies such as smart phones or navigation systems, automobiles today are transforming into so-called 'smart cars'. Smart cars are not just mechanical devices, but information media systems. The smart car is a prosthesis that assists the driver, enhancing the original function of the car, and provides a new place environment to the driver by composing a hybrid space where information space and actual space are fused. This article focuses on the fact that smart cars have all the media, functional, and spatial attributes. It is important to understand what smart car technologies are currently used and utilized by people, and how they affect drivers' perception. To examine the issue, an online survey of 340 drivers was conducted, with a focus on perceived control and attachment, as well as on the possession and the use of 14 smart car technologies. The results of hierarchical regression analysis reveal that the possession of smart car technologies influences on drivers' perception of control and attachment, regardless of the actual use. Based on the results, this article discusses the implications and the limitations, together with the practical suggestion for smart car system construction.
Keywords: 330; Smart car; use of media technologies; hybrid space; control; attachment